Think of consistent income generating investments after getting EPF - Borneo Post, (Kuching) (Borneo Post (Kuching), 2016)
ALOR SETAR: Employees Provident Fund (EPF) contributors must think of investment methods which brings a consistent monthly income after obtaining their EPF contributions or via other sources, upon retirement.